The Role of Information Technology Education in Preventing Child Grooming on Social Media - Ellyana Hawa; Frisca Lidya Amelia; Anisa Safira Rizky; Nuurin Lailatul Mufidah; Muhammad Anis Mukhson; M. Irfan Jazuli; Fathul Aziz (International Consortium of Education and Culture Research Studies, 2020)
The rapid development of information and communication technology, which has brought influence and change in the lives of people throughout the world. Influences and changes that occur due to the development of information and communication technology there are positive values, and there are also negative sides. In Indonesia, especially at this time, the development of information and communication technology has become a trend both among adults and young people. In addition to business, education and work related interests. Nowadays information and communication technology also plays an important role in socialization activities through various existing social networks. The problem is that social networking is now becoming a trend, especially for young people as an area where sexual offenders look for victims by exploiting the various characteristics of this virtual media. The role of information technology education itself in preventing child grooming on social media is to prevent crime in cyberspace (cyber crime) through a culture of computer use and a healthy Internet (Cyber ​​Health). Healthy internet is an activity in conducting online activities both browsing, streaming and downloading properly and in accordance with applicable laws and regulations, especially the Information and Electronic Transaction Law. , regulations and guidelines, and also supplemented by interviews with resource persons.